Assimilating Asians : Gendered Strategies of Authorship in Asian America - Chu, Patricia P. (Book collections on Project MUSE., 2000)
This work combines social theory with literary analysis to look at how Asian American writers use literature to participate in the critique and analysis of their position in US culture.